Optimizing DC-DC Converters through Interleaved Parallel Magnetic Integration: A Research Review - Nawaz, Muhammad Qasim; Khan, Aimal Khan (International Journal of Electrical, Energy and Power System Engineering, 2024)
One of the main areas of focus for power electronics development nowadays is interleaved parallel magnetic integration technology. On the basis of introducing the staggered parallel connection technology of internal combustion engines and power systems, the staggered parallel connection magnetic integration technology of power electronics is introduced. First, the interleaved parallel magnetic integration technology of various non-isolated and isolated DC-DC converters and their latest research results and applications are introduced; then, the three interleaved parallel technologies of internal combustion engines, power systems, and power electronics are compared; and finally, the current situation is pointed out. In China, research on interleaved parallel magnetic integration technology is not lagging behind internationally, but there is relatively little research on interleaved parallel magnetic integration technology for isolated DC-DC converters. It is recommended that research in this area be strengthened in the future. Looking to the future, the staggered parallel magnetic integration technology of power electronics will develop even more like the staggered parallel technology of internal combustion engines and power systems and make significant contributions to the development of industry and the national economy. Through this exploration, the paper aims to provide a critical analysis of the current state of research, offering valuable insights for engineers, researchers, and industry professionals involved in power electronics and converter design.